Students’ Lexical Choice Tendency and Ability to Distinguish British and American English Lexical - Tanti Nikmatul Zanah; Willyana Ramlan; Ela Nurmala (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2021)
This study aims to analyze the lexical choice tendency and ability to distinguish British and American English lexical. The participants were 20 students of the English Education Program in one of the state universities in Bandung. This research used the qualitative descriptive method to analyze the data. To collect the data, this research used tests as a technique. The lexical that were examined in the tests were based on Sukmawati (2017). The participants were given tests that were split into two parts in the form of multiple choices to examine the lexical choice tendency and measure the ability to distinguish British and American English lexical. The number of questions was 30 for each test, so the total number was 60 questions. The computation for the current study used simple calculation central tendency which was mean score, also a percentage, and tendency formula. The results show that the English Education Program students were able to be consistent in their lexical choice with most of the students tending to American English at the rate of 60%, followed by British English at the rate of 25%, and the rest 15% were still not able to be consistent in their lexical choice as they tend to Mix. The students were also able to distinguish British and American English lexical as they can attribute the examined lexical items to the right variety with the mean score of 58.5 that categorized into the average level. This indicates that the results of the current study are in contrast with Lindell (2014) who revealed the students tend to mix and are unable to distinguish British and American English lexical.